Characterisation of Swift Heavy Ion-induced Mixing using Secondary Ion Mass Spectrometry - Chakraborty, B. R.; Diva, K.; Kabiraj, D.; Avasthi, D. K. (Defence Science Journal, 2009)
Swift heavy ions of Au at 120 MeV are irradiated at the interface of Si/Me/Si (Me=V,Fe,Co) and the behaviour of mixing examined wrt to different ion doses. The fluences were varied from 1x1013 ions/cm2 to 1x1014 ions/cm2 on the multilayers of Si/Me/Se (Me=V,Fe,Co) and the interface of Si/Me(Me=V,Fe,Co) were characterised using Rutherford backscattering spectroscopy(RBS) and secondary ion mass spectrometry (SIMS). The atomic mixing width was found to be increasing monotonically with ion fluence in all the three cases,. The mixing rate and efficiency calculations were made and the diffusivity values thus obtained suggested a transient melt phase at the interface according to thermal spike model. In case of Me=Co, it was further probed with XRD and Raman spectroscopy to confirm the formation of cobalt silicides even at room temperature. Defence Science Journal, 2009, 59(4), pp.356-362, DOI:http://dx.doi.org/10.14429/dsj.59.1534